1998
DOI: 10.1002/(sici)1521-3765(19980710)4:7<1169::aid-chem1169>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

The Reaction of the [CpFe(CO)2]− Anion with Pentafluorochlorobenzene: Nucleophilic Aromatic Substitution by Halogen-Metal Exchange

Abstract: In the reaction of the [CpFe(CO) 2 ]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Experiments with polyfluorinated aryl and vinyl halides have been described previously. [21][22][23]26 [CpFe(CO) 2 ]K was obtained quantitatively (95-98%) by reductive cleavage of the dimer [CpFe(CO) 2 ] 2 with excess of NaK 2.8 alloy (0.10-0.15 ml per 1 mmol of dimer). 33 [Re(CO) 5 ]Na was prepared by the reduction of Re 2 (CO) 10 with 0.5% NaHg (30-50% excess) and purified by the low temperature crystallisation from THF.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Experiments with polyfluorinated aryl and vinyl halides have been described previously. [21][22][23]26 [CpFe(CO) 2 ]K was obtained quantitatively (95-98%) by reductive cleavage of the dimer [CpFe(CO) 2 ] 2 with excess of NaK 2.8 alloy (0.10-0.15 ml per 1 mmol of dimer). 33 [Re(CO) 5 ]Na was prepared by the reduction of Re 2 (CO) 10 with 0.5% NaHg (30-50% excess) and purified by the low temperature crystallisation from THF.…”
Section: Methodsmentioning
confidence: 99%
“…The yields of the products discussed above are purely spectroscopic, based upon the relative integral intensity of the signals of the products and the signal of internal standard (durene or (Me 3 Si) 2 O) in 1 H NMR spectra of reaction solutions. 21 The signals were referenced to the individual products by comparison to the spectra of the isolated compounds or with the literature data for the compounds previously described, including two iron carbonyl derivatives: PhCH=CHFe(CO) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By the use of anion traps (i.e, proton donors) and radical traps [25] they have been able to put forth a mechanism that challenges the traditional SET mechanism in favor of a HME mechanism (Scheme 1) [26]. The HME mechanism was shown to be the major pathway for Fp anion substitution of polyfluorinated aryl and alkenyl halides.…”
Section: Nucleophilicity Of the (η 5 -C 5 H 5 )(Co) 2 Fe Metalatementioning
confidence: 99%
“…We showed that nucleophilic substitution by carbonylates in perfluorinated aryl and vinyl halides can take place both as normal addition-elimination (Ad N E) (Scheme 1) and through nucleophilic attack by the carbonylate at the halogen atom (Hal = Cl, Br, I) (Scheme 2) [14][15][16][17].…”
mentioning
confidence: 99%